Genomic characterization of Sabiá virus in Brazil, 2019-2020: Implications for diagnostics, virus evolution, and receptor binding. - Claro,IM; Manuli,ER; da,Silva CAM; Coletti,TM; Lemey,P; Nastri,AC; Casadio,LVB; Duarte-Neto,AN; Quick,J; Romano,CM; Whittaker,C; Hill,SC; et al. (PLoS Negl Trop Dis, 2026)
Between December 2019 and January 2020, two patients suspected of having severe yellow fever were admitted to a tertiary healthcare facility in São Paulo, Brazil, presenting with acute hemorrhagic syndrome and neurological alterations; both cases had fatal outcomes. Upon admission, both tested negative for yellow fever viral RNA, and Sabiá virus (SABV), a New World arenavirus, was identified as the causative pathogen. To date, only four humans naturally acquired SABV infections have been confirmed, all fatal and linked to rural settings. We applied next-generation sequencing to generate complete and near-complete genomes from two patients (SP17 and SP19). Existing molecular diagnostics failed to detect SABV; therefore, new molecular tests were developed. Genetic analyses of SP17 and SP19 genomes along with other arenaviruses, revealed that the new cases were genetically diverse, showing 93-98.2% amino acid identity at the NP level among SP17, SP19, and the 1990 reference strain (SPH114202). Time-scaled phylogenetic analyses confirmed that SP17 and SP19 were not epidemiologically linked and suggested that SABV has been circulating undetected in Brazil for over a century. Additionally, homology modeling and structure-based mapping provided insights into SABV receptor-binding sequence conservation, suggesting that SABV shares similar receptor binding structure to other clade B arenaviruses, despite some amino acid variation around receptor binding site. Our findings underscore the need for retrospective and prospective surveillance of undiagnosed hemorrhagic fever cases to assess the public health impact of SABV in Brazil.